1994
DOI: 10.1128/mcb.14.5.3350
|View full text |Cite
|
Sign up to set email alerts
|

A novel mammalian protein, p55CDC, present in dividing cells is associated with protein kinase activity and has homology to the Saccharomyces cerevisiae cell division cycle proteins Cdc20 and Cdc4.

Abstract: A novel protein, p55CDC, has been identified in cycling mammalian cells. This transcript is readily detectable in all exponentially growing cell lines but disappears when cells are chemically induced to fall out of the cell cycle and differentiate. The p55CDC protein appears to be essential for cell division, since transfection of antisense p55CDC cDNA into CHO cells resulted in isolation of only those cells which exhibited a compensatory increase in p55CDC transcripts in the sense orientation. Immunoprecipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 78 publications
5
97
0
Order By: Relevance
“…Early studies have shown that p55CDC is associated with unknown protein kinase activities (Weinstein et al, 1994) and highly phosphorylated during the G 2 (Weinstein, 1997;Weinstein et al, 1994). We asked whether BUBR1 might be a candidate kinase that directly phosphorylated p55CDC.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Early studies have shown that p55CDC is associated with unknown protein kinase activities (Weinstein et al, 1994) and highly phosphorylated during the G 2 (Weinstein, 1997;Weinstein et al, 1994). We asked whether BUBR1 might be a candidate kinase that directly phosphorylated p55CDC.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that CDC20 is a target of the yeast spindle checkpoint (Hwang et al, 1998). Human p55CDC is a phosphoprotein and the phosphorylation peaks at G 2 (Weinstein, 1997;Weinstein et al, 1994). The phosphorylation drops signi®cantly as the cell enters mitosis (Weinstein, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations